UJI AKTIVITAS EKSTRAK AIR DESTILASIPADA JAMUR LINGZHI (Ganoderma lucidum)DENGAN MENGGUNAKANMETODE SOXHLET TERHADAP Proteus sp - Handrianto, Prasetyo (Journal of Research and Technology, 2018)
Infectious diseases health problem in developing countries such as in Indonesia one of them is Urinary Tract Infection (ISK). The cause of ISK is Proteus sp. This bacteria is one of the gram-negative causes of urinary tract infection (ISK). Urinary tract infections caused by Proteus sp are persistent, difficult to treat and can be died. Currently one of the natural ingredients known of the antimicrobial drug is the lingzhi mushroom (Ganoderma lucidum). The purpose of this study was to find out whether the concentration of lingzhi mushroom extract (Ganoderma lucidum)effect inhibition zone on bacteria Proteus sp. This anti-bacterial inhibitory test using disc diffusion method. The study was conducted with 6 replication and five concentrations is 20%, 40%, 60%, 80%, and 100%. The lingzhi mushroom (Ganoderma lucidum) extract using soxhlet method with distilled water solvent.Inhibition zone values at concentrations of 100 μg / ml were averaged 10.33 mm, 80 μg / ml of 9.8 mm, 60 μg / ml of 9.4 mm, 40 μg / ml of 8.2 mm, and 20 μg / ml of 8.03 mm. The average result is done by Anova One Way test obtained by result of value of sig, which means significant <0,05 then H0 there is no inhibition zone influence (rejected) and H1 there is inhibit zone effect (accepted). The LSD test results showed that the concentration of 40 μg/ml was significantly different with 60, 80, 100 μg/ml but not significantly different with the concentration of 20 μg/ml. The conclusion of this research is lingzhi mushrooom (Ganoderma lucidum)water ekstract have positive effect on proteus sp inhibition zone.